Functional loss of IκBε leads to NF-κB deregulation in aggressive chronic lymphocytic leukemia - Mansouri, Larry; Sutton, Lesley-Ann; Ljungström, Viktor; Bondza, Sina; Arngården, Linda; Bhoi, Sujata; Larsson, Jimmy; Cortese, Diego; Kalushkova, Antonia; Plevova, Karla; Young, Emma; Gunnarsson, Rebeqa; et al. (The Journal of experimental medicine, 2015)
NF-κB is constitutively activated in chronic lymphocytic leukemia (CLL); however, the implicated molecular mechanisms remain largely unknown. Thus, we performed targeted deep sequencing of 18 core complex genes within the NF-κB pathway in a discovery and validation CLL cohort totaling 315 cases. The most frequently mutated gene was NFKBIE (21/315 cases; 7%), which encodes IκBε, a negative regulator of NF-κB in normal B cells. Strikingly, 13 of these cases carried an identical 4-bp frameshift deletion, resulting in a truncated protein. Screening of an additional 377 CLL cases revealed that NFKBIE aberrations predominated in poor-prognostic patients and were associated with inferior outcome. Minor subclones and/or clonal evolution were also observed, thus potentially linking this recurrent event to disease progression. Compared with wild-type patients, NFKBIE-deleted cases showed reduced IκBε protein levels and decreased p65 inhibition, along with increased phosphorylation and nuclear translocation of p65. Considering the central role of B cell receptor (BcR) signaling in CLL pathobiology, it is notable that IκBε loss was enriched in aggressive cases with distinctive stereotyped BcR, likely contributing to their poor prognosis, and leading to an altered response to BcR inhibitors. Because NFKBIE deletions were observed in several other B cell lymphomas, our findings suggest a novel common mechanism of NF-κB deregulation during lymphomagenesis.
Keywords: Frameshift Mutation; I-kappa B Kinase; Gene Expression Regulation, Leukemic; buněčné jádro; signální transdukce; Gene Expression Profiling; Gene Deletion; lymfom z B-buněk marginální zóny; kinasa I-kappa B; Cohort Studies; výsledek terapie; DNA Mutational Analysis; NF-kappa B; Signal Transduction; Lymphoma, B-Cell, Marginal Zone; mutační analýza DNA; kohortové studie; Lymphoma, Mantle-Cell; Cell Nucleus; posunová mutace; delece genu; chronická lymfatická leukemie; cytoplazma; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Humans; B-buněčný lymfom; Leukemia, Lymphocytic, Chronic, B-Cell; receptory antigenů B-buněk; Chromosome Aberrations; viabilita buněk; chromozomální aberace; Cell Survival; stanovení celkové genové exprese; Receptors, Antigen, B-Cell; Cytoplasm; Lymphoma, B-Cell; Oligonucleotide Array Sequence Analysis; Treatment Outcome; regulace genové exprese u leukemie; lidé; lymfom z plášťových buněk